Respostas

2013-11-18T18:04:41-02:00
A) - x² + 8x - 15 < 0
a = - 1
b = 8
c = -15

x = -( 8) +- V 8² - 4 . -1 . -15 /2 . -1
x = -8 +- V 64 -60 / -2
x = - 8 + - V 4 / -2
x = - 8 + 2 / -2           x( -1)
x' = - 8 - 2 /2
x = - 10/ 2 = -5
x " = - 8 - 2 / - 2             x( -1)
x" = - 8 + 2 / 2 = 
x" = -6/2 = - 3
portanto x < 0 --- x = - 5 , - 3

b) x² - 6x + 9 > 0
  a= 1
b = -6
c = 9

x = -(-6) +- V -6² - 4 . 1 . 9 / 2 . 1
x = 6 +- V 36 - 36/2
x= 6 + - V0 /2
x" = 6 + 0 /2 = 3
x" = 6 - 0 /2 = 3          delta zero o reseultado do x' e x" são iguais
portanto x > 0 -- x = 3


c) x² + x - 12 >0

a = 1 
b = 1 
c = -12

x = - ( 1) +- V 1² - 4 . 1 . - 12 / 2 . 1
x = - 1 +- V 1 + 48 / 2
x = - 1 +- V 49/ 2
x = - 1 +- 7 / 2
x' = - 1 + 7 / 2 = 6 / 2 = 3
x" = - 1 - 7 / 2 = - 8 / 2 = - 4

para x > 0 -- x = 3
1 5 1